Utilization of Rosella as a Natural Color and Source of Antioxidants for Soybean Hull Nata - Nolita, Maurelle; Suharso, Eveline; Kurniawan, Christine J; Anugrahati, Nuri A.; Parhusip, Adolf J. N.; Soedirga, Lucia C.; Matita, Intan C. (Department of Technology of Agricultural product (THP) Jambi University, 2024)
Nata is a fiber-rich cellulose formed through the fermentation of sugar by Acetobacter xylinum bacteria. Soybean hull waste has a nutritional content of 14.45% protein, 3.04% fat, 3.15% ash, 47.01% crude fiber, and 32% total iron minerals, making it suitable as raw material in making nata sheets. Rosella flowers contain anthocyanins that can be used as a natural red colorant in food products. The addition of rosella flower crude extract to nata will increase the visual and functional values of nata. This study aims to determine the best concentration of rosella flower crude extract (0%, 2%, 4%, 6%) based on the characteristics and functional value of nata made from soybean hulls. The best concentration of rosella flower crude extract in this study is 6%, producing nata with 0.776±0.020 mM antioxidant, 2.230±0.276 mg/L anthocyanin, 67.40±0.063 L*, 48.84±0.740 °hue (red color), 13.96±0.770 C*. The scoring test results show that nata with 6% rosella flower crude extract has ‘slightly no foreign taste’ (4.55±1.197), ‘slightly no foreign aroma’ (4.80±0.966), and ‘slightly red’ color (4.20±0.687). The hedonic test results show that panelists ‘slightly like’ the taste (5,12±1,22), aroma (5,15±1,17), and color (5,57±1,11) of the nata.